Influence of the Skid Resistance of Ultrathin Wearing Course with Various Types of Asphalt Binders - Hongfu Liu; Teng Guo; Chenxi Yang; Yunyong Huang; Xuelian Li (Advances in Materials Science and Engineering)
Ultrathin wearing course (UTWC) has been widely applied in both asphalt pavements preventive maintenance and functional overlay. This study’s objective is to evaluate the influence of different modified asphalt binders with warm mix additives on the skid resistance of UTWC and to reveal the attenuation law of skid resistance of UTWC. Three types of modified asphalt binders (Styrene-Butadiene-Styrene- (SBS-) modified asphalt, Acrylester Rubber- (AR-) modified asphalt, and SinoTPS-modified asphalt) and sasobit warm mix asphalt additive were selected to prepare asphalt mixtures. The Model Mobile Load Simulator 3 (MMLS3) was used to simulate repeated vehicle loading and abrasion. The British Pendulum Number (BPN) and Mean Texture Depth (MTD) were chosen to evaluate the skid resistance of the UTWC. The Analysis of Range (ANOR) and Analysis of Variance (ANOVA) were used to verify the significance of asphalt binder on the antiskid performance of the UTWC. ANOR and ANOVA show that the influence of different modified asphalt binders on the skid resistance of the UTWC is significant. The SinoTPS modified asphalt mixture can maintain high texture roughness before and after abrasion, providing excellent and durable skid resistance. The influence of the addition of a warm mixing additive on the skid resistance of UTWC is not significant, and changes in microtexture mainly reflect its impact on antiskid performance. The decay curve of three modified asphalt binders of the skid resistance of the UTWC can be well fitted into an exponential function. The conclusion will play an essential role in selecting the asphalt binder in a UTWC to improve the antiskid performance.